Progression and Regression of Hepatic Lesions in a Mouse Model of NASH Induced by Dietary Intervention and Its Implications in Pharmacotherapy - Ding, Zhi-Ming; Xiao, Yue; Wu, Xikun; Zou, Haixia; Yang, Shurong; Shen, Yiyun; Xu, Juehua; Workman, Heather C.; Usborne, Amy L.; Hua, Haiqing (Frontiers in Pharmacology, 2018)
Understanding of the temporal changes of hepatic lesions in the progression and regression of nonalcoholic steatohepatitis (NASH) is vital to elucidation of the pathogenesis of NASH, and critical to the development of a strategy for NASH pharmacotherapy. There are challenges in studying hepatic lesion progression and regression in NASH patients due to the slow development of NASH in humans, one being the requirement for multiple biopsies during the longitudinal follow-up. Here we studied lesion progression and regression in the diet-induced animal model of NASH by application or removal of the pathogenic diet for multiple time periods. Male C57BL/6 mice fed Western diet developed progressive hepatic steatosis / macrovesicular vacuolation, inflammation, and hepatocyte degeneration, as well as perisinusoidal fibrosis and occasionally portal fibrosis as early as two months after initiation of the Western diet. In the same period, the mice exhibited elevated ALT (alanine aminotransferase) and AST (aspartate aminotransferase) enzyme activities, CK18 (cytokeratin – 18), PIIINP (N-terminal propeptide of type III collagen) and TIMP-1 (tissue inhibitor of metalloproteinase - 1). Hepatic steatosis diminished rapidly when the Western diet was replaced by normal rodent chow diet and hepatic inflammation and hepatocyte degeneration were also reduced. Interestingly, perisinusoidal fibrosis and portal fibrosis regressed eight months after chow diet replacement. To understand pharmacotherapy for NASH, mice with established NASH hepatic lesions were treated with either FXR agonist obeticholic acid (Ocaliva), or CCR2/5 antagonist Cenicriviroc. Similar to the diet replacement, metabolic modulator Ocaliva markedly reduced steatosis / macrovesicular vacuolation, hepatic inflammation, and hepatocyte degeneration effectively, but exhibited no significant effect on liver fibrosis. Anti-inflammation drug Cenicriviroc, on the other hand, markedly decreased inflammation and hepatocyte degeneration, and mildly decreased liver fibrosis, but exhibited no effect on hepatic steatosis / macrovesicular vacuolation. In conclusion, we found the progression of NASH hepatic steatosis / macrovesicular vacuolation, and inflammation eventually lead to hepatocyte death and fibrosis. Life style change and current pharmacotherapies in development may be effective in treating NASH, but their effects on NASH–induced fibrosis may be mild.